Advantages of low pressure carburising and high pressure gas quenching technology in manufacturing. (March 2014) - Hiller, G.
<x content-type="archive" xml:space="preserve">Abstract</x> Over the last decade, vacuum carburising in combination with high pressure gas quenching (HPGQ) has become a preferred technology in gear industry mainly in Europe and North America. Driven by cost savings in manufacturing of gears and shafts, the heat treatment process has gone into the focus of the manufacturers. The potential of savings in heat treatment is huge because the new technology allows the integration into the manufacturing chain of gears and shafts. With vacuum heat treatment furnaces is it possible to implement this integration into manufacturing. The advantages of vacuum technology are in particular: the absence of surface oxidation, the cold wall technology, the gas quenching technology, the reduced logistics, flexible reaction on the needs of production and the control of distortion. In parallel to the development of the new heat treat process, a second point came into the focus of manufacturers: the choice of material. The industry recognised that by choosing a slightly higher alloyed material, significant savings in the entire manufacturing chain can be realised: smaller grinding stock, faster carburising cycles, gas quenching with control of distortion, and ultimately the reduction/elimination of grinding- and straightening operations. Vacuum furnaces are flexible in their reaction to the production requirements. Only with these types of heat treatment furnaces is it possible to switch them off after use and save immediately energy and costs. This benefit was essential for the industry in 2008/09 during the world economic crisis. In the past, the automotive industry in Europe and North America mostly ran on conventional pusher type furnaces which must be kept on operating temperature even if only 50% of installed production capacity is needed. The vacuum furnace of type ModulTherm is a multi-chamber system and each chamber can be switched On or Off according to the production plan which finally saves a huge amount of cost for energy. This paper presents the advantages of the vacuum carburising technology with high pressure gas quenching. The author will demonstrate with examples and comparisons the benefits of vacuum technology and the successfully integration of heat treatment in the manufacturing chain.